Packaging reliability estimation of high-power device modules by utilizing silver sintering technology. (November 2020) - Lee, Chang-Chun; Kuo, Kuo-Shu; Wang, Chi-Wei; Chang, Jing-Yao; Han, Wei-Kuo; Chang, Tao-Chih
Abstract: A high-power packaging device composed of 600 V/450 A insulated gate bipolar transistor (IGBT) module is presented. Thermal dissipation is improved, and the temperature of junction declines after Ag paste sintering is applied instead of conventional soldering. A 100 μm-thick sintered Ag preform is utilized to assemble two IGBTs and two diodes on Al2 O3 direct bonded copper (DBC) substrate during reflow in a vacuum oven. Three DBCs are attached on a copper baseplate to construct a power module. After a thermal cycling test is conducted for up to 2000 cycles, the die shear strength of the sintered Ag is as high as 24.8 MPa. Lowering the induced stress to fracture failure by using finite element simulation is carefully suggested. Furthermore, the measured thermal resistance is reduced by approximately 22%, and the noise during the electrical performance is eliminated by using Ag sintering. This research reveals the successful application of Ag paste sintering in 600 V/450 A IGBT module. Highlights: A 600 V/450 A insulated gate bipolar transistor module is presented. Thermal and electrical properties of silver paste sintering are measured. Die shear strength of the sintered Ag is as high as 24.8 MPa is acquired. Scaling diode and preform thicknesses has a good advantage in releasing thermal stress. Lowering fracture failure is suggested using finite element simulation.